The Relationship of Family Support with Compliance with Fluid Limitations in Chronic Kidney Failure Patients in the Hemodialysa Room of Siti Fatimah Az-Zahra Hospital - Selamat Parmin; Serli Wulan Safitri; Nurhasanah (MultiTech Publisher, 2023)
Fluid restrictions cause patients with kidney failure to become stressed and anxious about facing a life-threatening disease. Family support is very much needed for patients with chronic kidney failure. Research Objective: To determine the relationship between family support and compliance with fluid restrictions in patients with chronic kidney failure in the hemodialysis room at Siti Fatimah Az-Zahra Regional Hospital, South Sumatra Province in 2023. Quantitative research method using analytical surveys and using correlational research with a cross sectional design. Research results: There is a significant relationship between family support and compliance with fluid restrictions in chronic kidney failure patients in the hemodialysis room at Siti Fatimah Az-Zahra Regional Hospital, South Sumatra Province in 2023 with a p.value of 0.016 and OR 5.769.